CFD modelling of flow structure and internal leakage paths for a swing compressor - Heng, Wan Teng (2019)
Computational fluid dynamics (CFD) has long been used as a tool to examine the operational performance of a newly designed device in terms of fluid behaviour. The benefits of using CFD include saving time and experimental cost as a prototype need not be created during the testing phase. Recently, rising concerns on environmental issues have highlighted the importance of energy efficient products. Hence, the minimisation of leakages in compressors has become one of the significant criteria in increasing volumetric efficiency. In this project, CFD was used as a tool to study leakages which occurred in a swing compressor. A model of a swing compressor was first created to understand the flow structure in the compression and suction chambers and the working fluid used was air. Prominent leakage paths in the compressor were then identified and parametric studies were conducted to study the effect of pressure and clearance sizes on the leakages across the leakage paths. Simulation results showed that as pressure and clearance sizes of radial clearance increases, mass flow rate across the clearance increases linearly. In the analysis of end face clearance, two variables were used to study the mass flow rate across clearance; a similar number of mesh layers across the clearance and equivalent cell layer thickness. Results from both variables were discussed and it was shown that the growth curves displayed a similar polynomial trend, indicating that an increment in pressure and clearance sizes affect the leakage rate across the clearances. Hence, it can be concluded that the dimension of clearances plays an essential role in the leakages of the swing compressor.